Modelagem computacional do transitório hidráulico de redes de distribuição de água utilizando o método lagrangeano das ondas características - Sanders Neto, Vicente de Castro (2019)
The Wave Characteristics Method (WCM) is a model comes to easy the physical comprehension and the water hammer calculus method, as well as the design of protective devices and the cavitation and column separation simulation; and, above all tasks, generate the results next to the Characteristics Method (MOC), which performs the calculations at each step of the simulation time. The WCM works based on the head loss equation as a function of Joukovsky's celerity, doing an analysis of the movement, transmission and reflection of the pressure waves from the excitation point to the ends of the water distribution network. By the way, this work can be done in a simulation of the computational processing of the hydraulic system in a water network and a result with the result obtained with MOC identifying the advantages and disadvantages of both. For the tests three examples were available in the literature, where the permanent regime is simulated directly in the EPANET program. In the transient regime, for the MOC and WCM tests, as the routines of the two models were implemented in the UFC7 program, which performs a computational model of the water hammer in Pipelines and Water Distribution Networks. As a result of the modeling of each network, considering the rapid placement of the valve, the WCM had results compared to the results generated by the MOC, regarding the estimates of maximum and minimum loads, generated, reach by reach, in UFC7. It is concluded that the WCM presents satisfactory results in relation to the MOC, requiring less computational importance and resulting in values of equal magnitude in the load wrappings. Despite the problems with the implementation of the WCM in spreadsheet calculation, it was possible to elaborate a routine in Java that calculates the MOC in networks of water distribution. What is more difficult than nets, enabling a faster and more accurate analysis of the hydraulic transient results.